Economic Evaluation of Bravo Geothermal Prospect in Participating Green Energy Effort - R. Fadhillaha, Ferdino; Tjendarsaa, Kin; Maya Damayantia, Sylviana; W. Adityatamab, Daniel; Purba, Dorman (GEMA EKONOMI, 2023)
Indonesia utilizes only 2.356 MW, around 8% of its geothermal resources. The government aims to increase geothermal power generation to 5.799 MW by 2030. Numerous geothermal projects, including Bravo, face challenges in achieving promising condition due to unfavorable economic returns. This study aims to find approach to make the Bravo geothermal project financially viable. It analyzes expenditures, financing strategies, revenue projections, depreciation, and taxes. The capital budgeting framework, employing discounted cash flow analysis, calculates economic indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Debt Service Coverage Ratio (DSCR). Sensitivity analysis identifies the most influential project parameter. The findings provide recommendations for achieving the required economic return. After implementing cost reductions and tax incentives, Bravo's current state reveals unviable equity situation with an NPV of -15.80 million USD and an IRR of 5.91% below the project's discount rate. While meeting lenders' requirements with DSCR of 1.3 and 14-year repayment period, additional efforts are needed. Approaches such as a 115% increase in the stage 1 tariff, 15% reduction in CAPEX, 2-year construction period acceleration, or 20-year license extension helps achieve the desired return. Negotiations with off-taker regulators and industry partnerships are crucial for executing these approaches